Novel Al-X alloys with improved hardness. (July 2020) - Hung, Cain J.; Nayak, Sanjeev K.; Sun, Yu; Fennessy, Colette; Vedula, Venkat K.; Tulyani, Sonia; Lee, Seok-Woo; Alpay, S. Pamir; Hebert, Rainer J.
Abstract: In this study, our goal is to design solid solution strengthened aluminum alloys for manufacturing technologies that involve high cooling rates. This investigation starts with an analysis of solid solution strengthening using first principles calculations to determine elastic property changes and local lattice distortions from the introduction of different elements into a host aluminum lattice. These results, coupled with both equilibrium and non-equilibrium solubility data, leads to the selection of cerium and cobalt as the primary candidate alloying elements. Alloys of AlCe and AlCo at concentrations of 0.5, 1.0, and 3.0 at. % are then synthesized and subjected to laser glazing to produce non-equilibrium microstructures. The microstructure and solid solution characteristics are determined using a combination of scanning electron microscopy and transmission electron microscopy. Furthermore, nanoindentation is used to measure the hardness showing that both candidate systems harden significantly after glazing. In addition, Al-1.0Co at. % achieves a hardness comparable to Al6061-T6. These results conclusively show that cerium and cobalt are promising elements in the next generation aluminum alloys which make use of non-equilibrium processing conditions such as additive manufacturing. Graphical abstract: Unlabelled Image Highlights: Design of new aluminum alloys using a combination of computational and experimental tools First-principles calculations reveal lattice strains for Al-X systems (X: elements), leading to selection of Co and Ce Laser surface glazing reveals phase formation and solubility extension for AlCo and AlCe systems Nanoclusters develop in rapidly quenched AlCo alloys that vary from fcc to Al9Co2 phase depending on alloy composition Hardness of Al-3at%Co laser glazed phase approximately twice that of Al6061-T6.